2021
DOI: 10.1186/s12890-021-01700-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxygen saturation compared to a prescribed target range using continuous pulse oximetry in acutely unwell medical patients

Abstract: Background Both inadequate and excessive administration of oxygen to acutely unwell patients results in risk of harm. Guidelines recommend titration of oxygen to achieve a target oxygen saturation (SpO2) range. Information regarding whether this is being achieved is limited. Methods In this two-centre non-interventional study we used continuous pulse oximetry in acutely unwell medical patients over a 24-h period to determine the proportion of time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While this trial captures favourable performance characteristics of the automated oxygen control system, the static nature of the testing and short 10 min testing period of the automated oxygen control function limits the applicability of the findings, as real-life situations where the Airvo-3 NIV device with OptiO 2 might best be used may pose more pronounced and enduring periods of hypoxaemia or hyperoxaemia. 6 While participants received automated oxygen control, a single SpO 2 range of 92%–96% was targeted so our findings may not be generalisable to other target ranges. Additionally, when participants received manual oxygen control, stepwise changes in FiO 2 were made at 6 min intervals, which does not reflect real-world clinician-initiated oxygen adjustment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…While this trial captures favourable performance characteristics of the automated oxygen control system, the static nature of the testing and short 10 min testing period of the automated oxygen control function limits the applicability of the findings, as real-life situations where the Airvo-3 NIV device with OptiO 2 might best be used may pose more pronounced and enduring periods of hypoxaemia or hyperoxaemia. 6 While participants received automated oxygen control, a single SpO 2 range of 92%–96% was targeted so our findings may not be generalisable to other target ranges. Additionally, when participants received manual oxygen control, stepwise changes in FiO 2 were made at 6 min intervals, which does not reflect real-world clinician-initiated oxygen adjustment.…”
Section: Discussionmentioning
confidence: 93%
“…In a standard medical ward, adjusting oxygen manually appears suboptimal, with SpO 2 target range maintained only around half the time. 6 This compares to intensive care units (ICUs), where manually adjusted oxygen under clinical trial conditions has been reported to maintain SpO 2 within target range approximately 90% of the time, 7 while in a cohort study, adherence to the target SpO 2 range was achieved only 43% of the time. 8 Novel automated oxygen control systems have been developed, operating an algorithm-based closed-loop controller that automatically titrates the delivered fractional concentration of inspired oxygen (FiO 2 ) to maintain SpO 2 within a prespecified target range.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 95%
See 1 more Smart Citation
“…In a complementary way, definition of the saturation target in the prescription is also important to assess the need to use oxygen therapy, or the possibility for suspension or weaning. When a patient does not have a SatO 2 target defined, they may receive excessive oxygen therapy, which is associated with a higher risk of mortality, mainly in patients at risk of hypercapnic respiratory failure, or insufficient oxygen therapy 17 . Such being the case, it is imperative that all patients in use of supplemental oxygen are monitored and that oximetry is performed on a regular basis, which should be considered as the "fifth vital sign", so that oxygen is titrated to the target saturation defined 2,6 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 In contrast, SpO 2 was maintained within the target range for only 56 % of time in medical in-patients receiving HFNOT. 8 …”
Section: Introductionmentioning
confidence: 99%